A new genus and species of Xyphosiini (Diptera: Tephritidae) from Iran - Memari, Fatemeh; Namin, Saeed Mohamadzade; Hakimitabar, Masoud (Zootaxa, 2016)
Valera, a monotypic new genus (Tephritidae, Tephritinae, Xyphosiini) and Valera ariana n. sp., the type and only known species, are described from Iran. Systematic relationships with other Xyphosiini are discussed and a key to the genera of the tribe Xyphosiini is presented.